(untitled) (AYUSHDHARA, 2024)
Polycystic ovarian syndrome is disorder that affects the whole life of a female, can begin in utero in genetically predisposed subjects, manifests clinically at puberty, and continues during the reproductive years. According to Ayurveda can be considered under Agni vaishamyajanya vikara and it can consider as Beeja kosha granthi. The basic concept of Ayurveda is Hetu-linga and Aushadha to make diagnosis and to cure this disorder. Excess Kapha dusthikara nidana overall causes Agnimandhya, then this causes Amotpatti (free radicals in body). Aam causes Artavavaha srotas rodha, these causes Dhatvagnimandhya and as a result Apachit ras dhatu and Uttarotara dhatu apachana leading to Meda dhatu dushti and Alpartava. Triphala and Guggulu act on Meda dhatu, Medohara in property. This proved to be act on adiponectin. 5-7% reduction in weight improves symptom of PCOS effectively. Pathya like Masha, Tila, Matsya, Kulatha, Udvisha, Dadhi, Sura, fruits helps in increasing the Agneyatwa of aartava dhatu. Organs involved in PCOS is ovary, adrenal gland, pancreas and pituitary gland, Agni of these organs are affected by modern stressful lifestyle. Ayurveda protocols of Dincharya, Ritucharya, Swastwrit, Acharya rasayan, Tri upsthambh- Aahara, Nidra and Bhrahmcharya, Shodhasha sanskara, Rajaswala paricharya, Garbhini paricharya, Sutika paricharya etc should be maintained for remaining disease free and to improve quality of life of a female, for making healthy female, healthy family and healthy nation.